2009
DOI: 10.4028/www.scientific.net/amr.71-73.489
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Metal Recovery from Laterite Tailings by Bioleaching

Abstract: In previous studies it has been showed that sulphuric bio-acid is a good leaching agent for laterite tailings. In this work we evaluated nickel and cobalt recoveries from tailings of Caron technology process using sulphuric acid produced by Acidithiobacillus thiooxidans cultures under different conditions. In studies where tailings were initially added to the cultures, high nickel and cobalt recoveries (about 60 % for cobalt and 85-100 % for nickel) were reached after 13 days when low pulp densities (1 % and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(15 reference statements)
0
3
0
1
Order By: Relevance
“…Earlier studies by Hernández et al [27] showed that bioleaching of Ni and Co from CARON process residue with A. thiooxidans in a one-stage batch system was inversely proportional to the increase in pulp density (1%, 2.5%, 5% and 10%). Leaching was not observed at the highest concentration added (10%) and the results with 10% pulp density were identical to the abiotic control.…”
Section: Bioleaching In Two-stage Batch Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies by Hernández et al [27] showed that bioleaching of Ni and Co from CARON process residue with A. thiooxidans in a one-stage batch system was inversely proportional to the increase in pulp density (1%, 2.5%, 5% and 10%). Leaching was not observed at the highest concentration added (10%) and the results with 10% pulp density were identical to the abiotic control.…”
Section: Bioleaching In Two-stage Batch Systemmentioning
confidence: 99%
“…For this reason, A. thiooxidans has been widely used in the bioleaching of low-grade and concentrates of sulphide minerals on both laboratory and industrial scales [21][22][23]. This bacterium has also been used to solubilise nickel and cobalt from wastes from the mining-metallurgy industry, including lateritic overburden [24] and tailings [25][26][27]. The aim of the work described here was to evaluate the capacity of A. thiooxidans DMS 11478 to recover the heavy metals contained in the residues 0304-3894/$ -see front matter © 2011 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…• direct bioleaching in which an autotrophic acidophile supplied with sulfur or another RISC produced sulfuric acid for the extraction of metals from mine waste or tailings [344,[396][397][398][399][400]];…”
Section: Waste and Tailings From Oxidised Oresmentioning
confidence: 99%
“…Chen y Lin 63 también informaron que el aumento de la cantidad de azufre da como resultado un aumento de la tasa de acidificación, la producción de sulfato y solubilización de metales. Los datos aportados por Hernández Díaz et al64 muestran que el incremento en la densidad de pulpa de azufre de los cultivos, produce una mayor solubilización de metales. Pero a pesar de que un aumento de la cantidad de azufre agregada genera una acidificación eficiente y solubilización de metales en el proceso de biolixiviación, también implica un aumento en los costes operativos y obstaculiza la eliminación de los sedimentos tratados63 .…”
unclassified